Aberrant Expressions and Variant Screening of SEMA3D in Indonesian Hirschsprung Patients - Gunadi,; Kalim, Alvin Santoso; Budi, Nova Yuli Prasetyo; Hafiq, Hamzah Muhammad; Maharani, Annisa; Febrianti, Maharani; Ryantono, Fiko; Yulianda, Dicky; Iskandar, Kristy; Veltman, Joris A. (Frontiers in Pediatrics, 2020)
Background: The semaphorin 3D (SEMA3D) gene has been implicated in the pathogenesis of Hirschsprung disease (HSCR), a complex genetic disorder characterized by the loss of ganglion cells in varying lengths of gastrointestinal tract. We wished to investigate the role of SEMA3D variants, both rare and common variants, as well as its mRNA expression in Indonesian HSCR patients. Methods: Sanger sequencing was performed in 54 HSCR patients to find a pathogenic variant in SEMA3D. Next, we determined SEMA3D expression in 18 HSCR patients and 13 anorectal malformation colons as controls by quantitative real-time polymerase chain reaction (qPCR). Results: No rare variant was found in the SEMA3D gene, but one common variant in exon 17, p.Lys701Gln (rs7800072). The risk allele (C) frequency at rs7800072 among HSCR patients (23%) was similar to those reported for the 1000 Genomes (27%) and ExAC (28%) East Asian ancestry controls (p=0.49 and 0.41, respectively). A significant different of SEMA3D expression was observed between groups (p=0.04). Furthermore, qPCR revealed that SEMA3D expression was strongly up-regulated (5.5-fold) in the ganglionic colon of HSCR patients compared to control colon (CT 10.8 ± 2.1 vs. 13.3 ± 3.9; p=0.025). Conclusions: We report the first study of aberrant SEMA3D expressions in HSCR patients and suggest further understanding into the contribution of aberrant SEMA3D expression in the development of HSCR. In addition, this study is the first comprehensive analysis of SEMA3D variants in the Asian ancestry.